2021
DOI: 10.28991/cej-2021-03091756
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Conveyance Losses from Tertiary Irrigation Network

Abstract: Irrigation canals are generally made through porous soil formations, since the soil is loose porous media – a huge amount of canal water is lost to conveyance losses. The situation becomes direr when these losses result in non-beneficial losses. The Sindh province of Pakistan has more than 70% saline groundwater, conveyance losses to such areas in the province not only become unusable but also creates water management problems. Perhaps the only cost-effective way to address these losses is canal lining. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…(13) Water regulation. Water regulation service is mainly defined as the regulation of hydrological flows at the earth surface by land-cover, maintaining 'normal' conditions [34,35]. As there is no exchange value in trade, avoided cost can be used in this paper to evaluate it.…”
Section: Plos Onementioning
confidence: 99%
“…(13) Water regulation. Water regulation service is mainly defined as the regulation of hydrological flows at the earth surface by land-cover, maintaining 'normal' conditions [34,35]. As there is no exchange value in trade, avoided cost can be used in this paper to evaluate it.…”
Section: Plos Onementioning
confidence: 99%
“…Most irrigation channels worldwide are made of loose soil formations. Since the soil is a loose porous medium, a significant amount of freshwater seeps down through soil pores via channel bed and banks; in the process, a significant amount of precious freshwater resources is lost (Syed et al, 2021). Thus, the irrigation system water conveyance efficiency is not fully achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Knowing that Pakistan has a vast network of earthen irrigation channels to convey irrigation water from its source to farmlands, a substantial amount of good quality canal water is lost annually by seepage (Shah et al, 2020). Syed et al (2021) observed over 40% water losses from tertiary irrigation networks in Sindh, Pakistan whereas Shah et al (2020) observed over 45% water losses from distributary canals in Punjab, Pakistan. Seepage reduces the canal conveyance efficiency, diminishing water availability for agricultural purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Water utilities in developing countries face significant challenges and adverse effects of water losses in WDSs. The most appropriate water loss management (WLM) strategy should be defined in order to provide reliable water supply to customers and to establish an efficient operation plan (Mutikanga et al 2010;Syed et al 2021). NRW has significant adverse effects on economic losses, water resource and energy inefficiency, and safety of water service in WDS.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%